How to use good Japanese (The International Students Institute Japan, 1979)
This book consists of the text and its references. In the first 15 lessons, the text proper is written in Romaji. In and after lesson 16, the contents of this book have been mostly abridged from the " Nihongo rio Hanshikata",...